(untitled) (El Taco en la Brea, 2025)
The objective of the following work is to carry out a metacritical reading of the concepts of archive and canon in contemporary Argentinean literary studies. Starting from an exploratory hypothesis about the inflation of the archive and the strategic deflation of the canon in the present, the work, through the affirmation of a discursive materialism, adjusts its initial intuition to the different critical activations: from the affirmation of an archival turn that it apparently makes the canon device obsolete, going back to the reevaluations of the canon in recent decades, up to the recent proposals for the complementarity of the two concepts.